Simulation of in-plane vibrations of 2D structural solids with singularities using an efficient wave based prediction technique - Vanmaele, Caroline; Vergote, Karel; Vandepitte, Dirk; Desmet, Wim (Computer Assisted Methods in Engineering and Science, 2012)
This paper proposes the wave based method for the steady-state dynamic analysis of the in-plane behaviour of 2D structural solids. This novel prediction technique relaxes the frequency limitations of the commonly used finite element method through an improved computational efficiency. This efficiency is obtained by selecting basis functions which satisfy the governing equations a priori, in accordance with the indirect Trefftz approach. Special attention is paid to problems in which singularities appear in the problem solution. For these problems, the conventional set of basis functions is extended with functions which can represent the singularity accurately. The capabilities of this novel method for mid-frequency applications, as compared to the standard finite element method, are demonstrated by means of two numerical examples.